Analysis of The Integrated Farming Income in The SMD (Sarjana Membangun Desa) Program In Padang City (Case Study: Tani Ternak Sepakat Group) - Amelira Haris Nasution; Nofialdi Nofialdi; Ferdhinal Asful (Indonesian Journal of Agricultural Research, 2019)
The purpose of this research is to analyze the farming income of farmers who develop integrated farming system after and before getting the SMD Program in Padang City by involving Tani Ternak Sepakat Group as case study. This research was designed as a case study conducted from June 2012 to July 2012 in Kurao Pagang, Padang City, West Sumatera. In this research, the researcher used descriptive qualitative and descriptive quantitative design. The results of this study showed that the integrated farming system through the SMD Program in Tani Ternak Sepakat Groups has implemented the integration between paddy farming and breeding funded by SMD Program. For breeding activity, The Tani Ternak Sepakat group raises both goats and cows. At the same time, the farmer group also cultivates paddy only for integrating between paddy farming and cattle. The integration is done through the use of cattle’s compost as paddy farming fertilizer and the use of paddy’s farming residues for feeding the cattle. However, these practices reduce farmers’ income by 95.12% for the first years of the program. Based on the study, it is suggested that farmers implement waste treatment technology that utilize available resources and to increase their income. Key Word: SMD Program, Integrated Farming System, Farmers Income